Protocolo de monitorização clínica da artrite reumatóide (PMAR) - Revisão de Dezembro de 2007 - Fonseca, J E (2007)
The authors present the update of a protocol for the clinical follow-up of Rheumatoid Arthritis Patients (PMAR) which aims to contribute to a standardized clinical observation of these patients, particularly when they are being treated with biologic therapies.